2020
DOI: 10.21203/rs.3.rs-71849/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facile investigation of reversible nanostructure changes in flexible crystals

Abstract: Detailed investigation of macroscopic deformation and nanoscopic structural changes in flexible organic crystals pose challenges for investigators. Herein, applied stress and subsequent relaxation of elastic organic crystals resulted in reversible macroscopic crystal deformation. X-ray diffraction with a curved jig revealed reversible nanoscopic structural changes in the crystal structure under the bending stress and relaxation. The crystal lattice changed quantitatively under the applied macroscopic stress-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For preparing a fluorescent microresonator (FM) in the present research, β-cyano-appended oligo­( p -phenylenevinylene) (β-COPV) is used as a fluorescent dopant (Figure a) . The electronic absorption spectrum of a CHCl 3 solution of β-COPV shows two bands at 348 and 432 nm, which are attributed to π-π* and intramolecular charge-transfer transitions, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…For preparing a fluorescent microresonator (FM) in the present research, β-cyano-appended oligo­( p -phenylenevinylene) (β-COPV) is used as a fluorescent dopant (Figure a) . The electronic absorption spectrum of a CHCl 3 solution of β-COPV shows two bands at 348 and 432 nm, which are attributed to π-π* and intramolecular charge-transfer transitions, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…A photoluminescence (PL) spectrum of COPV in CHCl 3 features a unimodal emission band (Figure 2b, green solid line) centered at 515 nm, while the PL band in a solid state (Figure 2b, orange solid line) is centered at 607 nm due to the intermolecular donor-acceptor interaction. [26] COPV exhibits an aggregation-induced enhanced emission (AIEE) behavior: [27,28] The PL quantum yield (φ) of COPV in the solid state (0.95) is much larger than that in the solution state (0.41). The excellent φ of COPV crystal is particularly beneficial for developing optical experiments.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The single crystal of COPV belongs to triclinic system with a space group of P-1 (for detailed crystallographic data, see Table S1, Supporting Information), which was reported previously by one of the authors. [26] The constituent COPV molecules in FOC COPV stack on one another via π-π interactions to form a 1D column along the crystallographic a-axis (Figure S2b-e, Supporting Information). A powder X-ray diffraction (PXRD) profile of FOC COPV shows distinct diffraction peaks at 7.1°, 9.2°, and 18.5°, which are assignable to (001), (010), and (020) planes, respectively (Figure S2a, Supporting Information).…”
Section: Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Worthy et al [55] found that there is a qualitative difference in the crystal structure by investigating from elongation at the outside to contraction at the inside by focusing the beam in X-ray structural analysis of the bent cupper acetylacetonate, Cu(acac) 2 , crystal. The author proposed a facile method for investigating nanostructure changes of flexible organic crystals by using readily accessible X-ray equipment [56]. X-ray diffraction (XRD) with a curved jig, which applied macroscopic stress-strain (%), revealed reversible and quantitative crystal structure changes under bending stress and relaxation.…”
Section: Detailed Deformation Of Elastic Organic Crystalsmentioning
confidence: 99%